Regional rural development: The need for deregulation - Karl Fasbender (Intereconomics, 1985)
Government intervention in developing countries has often been biased towards the support of urban industries and the urban population. The resulting distortions in exchange rates and in the prices of the factors of production have had serious detrimental effects on rural areas. A gradual deregulation of prices is necessary if the problems of the rural areas are to be overcome.
Keywords: 330; Development Strategy